The Effect of the Implementation of Environmental Accounting on Profitability in Mining Sector Companies Listed on the Efek Indonesia Exchange - Rejeki, Dewi; Nurlatifah, Siti (Ilomata International Journal of Tax and Accounting, 2024)
Mining sector companies have an important role for the country, because the contribution given is very significant and affects economic growth in Indonesia. This mining sector company has an impact on the continuous use of natural resources, even though the available natural resources are very limited to meet human needs and take a long time to renew. Based on the development of profitability of mining sector companies in Indonesia for four years, from 2019-2022 there was a decrease in profitability in 2019-2020. This decrease was caused by several factors, including the COVID-19 pandemic, contract delays and cancellations, the company's awareness of environmental activities decreased resulting in a decrease in company awareness of social and environmental which included environmental costs, environmental disclosure, and environmental performance. The reason of this observe is to prove the impact of the implementation of green environmental costs, environmental disclosure, and environmental performance on profitability in mining sector companies listed on the company's Indonesia Stock Exchange as well as the Indonesia Stock Exchange. The approach used is a quantitative technique using secondary statistics in the shape of reports and annual reports on mining area corporations indexed on the Indonesia Stock Exchange (IDX) the duration ofc2019-2022 as many as 32 samples. The data analysis techniques used are descriptive statistical tests and multiple linear regression tests. The outcomes of this observe prove that partly environmental costs have a negative and significant impact on profitability, environmental disclosure has no impact on profitability, environmental performance has a positive have an effect on profitability. Simultaneously, environmental expenses, environmental disclosure, and environmental overall performance concurrently or collectively have an significant impact on profitability.